RETRACTED: A Deep Learning Model for Three-Dimensional Nystagmus Detection and Its Preliminary Application - Lu, Wen; Li, Zhuangzhuang; Li, Yini; Li, Jie; Chen, Zhengnong; Feng, Yanmei; Wang, Hui; Luo, Qiong; Wang, Yiqing; Pan, Jun; Gu, Lingyun; Yu, Dongzhen; et al. (Frontiers in Neuroscience, 2022)
Symptoms of vertigo are frequently reported and are usually accompanied by eye-movements called nystagmus. In this article, we designed a three-dimensional nystagmus recognition model and a benign paroxysmal positional vertigo automatic diagnosis system based on deep neural network architectures (Chinese Clinical Trials Registry ChiCTR-IOR-17010506). An object detection model was constructed to track the movement of the pupil centre. Convolutional neural network-based models were trained to detect nystagmus patterns in three dimensions. Our nystagmus detection models obtained high areas under the curve; 0.982 in horizontal tests, 0.893 in vertical tests, and 0.957 in torsional tests. Moreover, our automatic benign paroxysmal positional vertigo diagnosis system achieved a sensitivity of 0.8848, specificity of 0.8841, accuracy of 0.8845, and an F1 score of 0.8914. Compared with previous studies, our system provides a clinical reference, facilitates nystagmus detection and diagnosis, and it can be applied in real-world medical practices.